Void Handling by Utilizing Location-Based Assistance Through Trajectory Mapping - Phonepadith Phoummavong; Vimontha Khieovongphachanh; Khanthanou Luangxaysana; Phouthong Southisombath; Sathaporn Promwong (My University, 2023)
The Ad hoc Networks (MANETs) rely heavily on location-aided routing protocols due to their energy-saving capabilities and ability to extend the network lifetime, especially in emergency situations where private IP addresses are unavailable. However, the route discovery process of the location-aided routing (LAR) is ineffective in void zone environments where data packets cannot reach their intended destination. To address this issue, this paper presents a new approach called Location-aided base on trajectory that eliminates the void zone. The results demonstrate that the proposed method outperforms existing approaches in terms of reachability, making it a more robust alternative to the default location-aided routing protocol.
Keywords: Mobile Ad Hoc Networks; Opportunistic and Delay-Tolerant Networks; Energy Efficient Wireless Sensor Networks